Highly Sensitive Detection of Polarized Light Using Anisotropic 2D ReS2 - Liu, Fucai; Zheng, Shoujun; He, Xuexia; Chaturvedi, Apoorva; He, Junfeng; Chow, Wai Leong; Mion, Thomas R.; Wang, Xingli; Zhou, Jiadong; Fu, Qundong; Fan, Hong Jin; Tay, Beng Kang; et al. (Advanced functional materials, 2016)
Due to the novel optical and optoelectronic properties, 2D materials have received increasing interests for optoelectronics applications. Discovering new properties and functionalities of 2D materials is challenging yet promising. Here broadband polarization sensitive photodetectors based on few layer ReS2 are demonstrated. The transistor based on few layer ReS2 shows an n‐type behavior with the mobility of about 40 cm2 V−1 s−1 and on/off ratio of 105. The polarization dependence of photoresponse is ascribed to the unique anisotropic in‐plane crystal structure, consistent with the optical absorption anisotropy. The linear dichroic photodetection with a high photoresponsivity reported here demonstrates a route to exploit the intrinsic anisotropy of 2D materials and the possibility to open up new ways for the applications of 2D materials for light polarization detection. Polarization sensitive photodetectors are demonstrated based on anisotropic few‐layer ReS2. The transistor based on few layer ReS2 shows an n‐type behavior with a mobility of about 40 cm2 V−1 s−1 and photoresponsivity of about 103 A W−1. The polarization dependence of photoresponse is ascribed to the unique anisotropic structure. The result demonstrates a route to exploit the intrinsic anisotropy of 2D materials and the possibility to open up new ways of the applications of 2D materials for light polarization detection.